Influence of squeeze cast process parameters on wear behavior of AA6061. (2020) - Thirumal Azhagan, M.; Mohan, B.
Abstract: The automobile and aeronautical sectors have simulated the emergence of processes that yield defect free components. Squeeze casting is one such novel process that is mostly adopted to produce light weight alloys of Aluminium and Magnesium. The influence of squeeze cast process parameters on wear behavior of AA6061 was investigated in this study by employing Taguchi method. The process parameters considered in this study were pressure, die temperature and pressure duration respectively. L9 (3 4 ) orthogonal array of Taguchi method was chosen to conduct the experiments and the squeeze cast components were produced. The pins were made from these components and they were subjected to wear test. The wear rate was obtained from the weight loss of the pin. The analysis showed that the parameters such as pressure and die temperature caused appreciable improvement towards the wear resistance exhibited by AA6061 components.